Iron, zinc and copper in the Alzheimer’s disease brain: a quantitative meta-analysis. Some insight on the influence of citation bias on scientific opinion - Schrag, Matthew (2011)
Dysfunctional homeostasis of transition metals is believed to play a role in the pathogenesis of Alzheimer’s disease (AD). Although questioned by some, brain copper, zinc, and particularly iron overload are widely accepted features of AD which have led to the hypothesis that oxidative stress generated from aberrant homeostasis of these transition metals might be a pathogenic mechanism behind AD. This meta-analysis compiled and critically assessed available quantitative data on brain iron, zinc and copper levels in AD patients compared to aged controls. The results were very heterogeneous. A series of heavily cited articles from one laboratory reported a large increase in iron in AD neocortex compared to age-matched controls (p<0.0001) while seven laboratories failed to reproduce these findings reporting no significant difference between the groups (p=0.76). A more than three-fold citation bias was found to favor outlier studies reporting increases in iron and this bias was particularly prominent among narrative review articles. Additionally, while zinc was not significantly changed in the neocortex (p=0.29), copper was significantly depleted in AD (p=0.0003). In light of these findings, it will be important to re-evaluate the hypothesis that transition metal overload accounts for oxidative injury noted in AD.